Outcomes of the Victo™ adjustable artificial urinary sphincter in the treatment of male incontinence - Krhut, Jan; Bartáková, Lucie; Kondé, Adéla; Sýkora, Radek Paus; Rychlý, Tomáš; Zachoval, Roman (BJU international, 2025)
OBJECTIVES: To report the clinical outcomes of the Victo™ (Promedon, Cordoba, Argentina) adjustable artificial urinary sphincter (AUS) implantation in a cohort of patients with severe urinary incontinence (UI) after prostate surgery. PATIENTS AND METHODS: This study enrolled patients with UI following prostate surgery who underwent a Victo implantation between May 2018 and December 2023. Patients were prospectively evaluated at baseline, and at 3 and 12 months after device activation, and thereafter annually. The 24-h pad-weight test (24hPWT) was used to assess severity of UI, while the Patient Global Impression of Improvement (PGI-I) and patient satisfaction according to a Likert scale were used to measure patient-reported outcomes. RESULTS: A total of 96 patients with a median (interquartile range [IQR]) age of 68 (65-72) years were included in the final analysis. The median (IQR) follow-up was 3 (1-4) years. In all, 10 patients completed the 5-year follow-up. After the treatment, we observed a significant reduction in 24hPWT by the median of 83% (P < 0.001) at 3 months and by a median of 79% (P < 0.001) at 3 years. According to the PGI-I, a total of 87%, 92%, 87%, 81%, 83%, and 50% (five of 10) of patients rated their condition/incontinence as 'very much improved', 'much improved' or 'little improved' at 3 months, 1-, 2-, 3-, 4-, and 5-year follow-up visits, respectively. The proportion of patients, who were 'very satisfied' or 'satisfied' with the treatment outcome was 79%, 80%, 75%, 69%, 80%, and 60% (six of 10) at 3 months, 1-, 2-, 3-, 4-, and 5-years, respectively. There were a total of 13 (14%) device failures during the follow-up period. CONCLUSION: In conclusion, our data suggest that Victo AUS significantly reduces the severity of UI after prostate surgery and provides a reasonably high patient-reported satisfaction with treatment outcomes at mid-term follow-up.
Keywords: Patient Satisfaction; Humans; artificial urinary sphincter; lidé středního věku; Aged; pad‐weight test; výsledek terapie; senioři; lidé; urinary incontinence; spokojenost pacientů; inkontinence moči; Prostatectomy; Urinary Incontinence; Postoperative Complications; pooperační komplikace; Male; Middle Aged; Treatment Outcome; umělý močový svěrač; prostatektomie; patient‐reported outcomes; mužské pohlaví; prospektivní studie; Urinary Sphincter, Artificial; radiotherapy; Prospective Studies